2015
DOI: 10.1186/s12896-015-0164-6
|View full text |Cite|
|
Sign up to set email alerts
|

Rapid high-yield expression of a candidate influenza vaccine based on the ectodomain of M2 protein linked to flagellin in plants using viral vectors

Abstract: BackgroundThe extracellular domain of matrix protein 2 (M2e) of influenza A virus is a promising target for the development of a universal vaccine against influenza because M2e sequences are highly conserved among human influenza A strains. However, native M2e is poorly immunogenic, but its immunogenicity can be increased by delivery in combination with adjuvants or carrier particles. It was previously shown that fusion of M2e to bacterial flagellin, the ligand for Toll-like receptor (TLR) 5 and powerful mucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 42 publications
0
36
0
2
Order By: Relevance
“…Previous studies of M2e-based vaccines demonstrated substantially different results depending on the experimental animal model used. The use of M2e-based vaccines alone in mouse models confers protection against HPAI and low pathogenic avian influenza (LPAI) virus challenge, making them candidate universal influenza A vaccines [6, 16, 28, 29]. However, challenge studies in chickens have demonstrated protection against LPAI but not HPAI, although antibodies elicited by M2e-based vaccines were induced in immunized chickens [7, 30, 31].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of M2e-based vaccines demonstrated substantially different results depending on the experimental animal model used. The use of M2e-based vaccines alone in mouse models confers protection against HPAI and low pathogenic avian influenza (LPAI) virus challenge, making them candidate universal influenza A vaccines [6, 16, 28, 29]. However, challenge studies in chickens have demonstrated protection against LPAI but not HPAI, although antibodies elicited by M2e-based vaccines were induced in immunized chickens [7, 30, 31].…”
Section: Discussionmentioning
confidence: 99%
“…This allows relatively fast characterization of libraries of genetic components in a common genetic background (Sparkes et al 2006;Engler et al 2014;Brückner et al 2015). Transient leaf agroinfiltration in Nicotiana has been adopted as an efficient method for the optimization of metabolic pathways, such as artemisinin (van Herpen et al 2010) and triterpene biosynthesis pathways (reviewed in Thimmappa et al 2014), and the bioproduction of vaccines (D'Aoust et al 2008, Mardanova et al 2015. Large investments have been made in both the private and the public sectors to scale up production for vaccines against viruses like Ebola (ZMapp, Mapp Biopharmaceuticals) and influenza (Medicago).…”
Section: Nuclear Transformation In Plantsmentioning
confidence: 99%
“…с соавт. продемонстрировала иммуногенность и протективность химерного белка, состоящего из 4 аминокислотных по-следовательностей М2е (2 последовательнос-ти М2е консенсусные между человеческими штамма вируса гриппа А и 2 последовательнос-ти М2е от штамма A/Chicken/Kurgan/05/2005), соединенных с аминокислотной последова-тельностью белка флаггелина от Salmonella typhimurium [60]. Данная химерная конструк-ция была получена при помощи экспрессии плазмидного вектора в растении Nicotiana benthamiana.…”
Section: кандидатные вакцины на основе м2еunclassified
“…Данная химерная конструк-ция была получена при помощи экспрессии плазмидного вектора в растении Nicotiana benthamiana. Трехкратная иммунизация мы-шей 10 мкг полученного препарата индуцирует выработку М2е-специфичных антител и обес-печивает 75%-ную защиту против 5ЛД 50 [60]. Имеются данные о том, что кандидатная уни-версальная вакцина на основе химерных но-ровирусных частиц, модифицированных кон-сенсусным птичьим М2е (М2е-РР), способна индуцировать выработку значимых титров IgG у кур при подкожном введении в сочетании с масляным адъювантом [16].…”
Section: кандидатные вакцины на основе м2еunclassified